Real-Life Use of Ceftolozane/Tazobactam for the Treatment of Bloodstream Infection Due to Pseudomonas aeruginosa in Neutropenic Hematologic Patients: a Matched Control Study (ZENITH Study) - Alba Bergas; Adaia Albasanz-Puig; Ana Fernández-Cruz; Marina Machado; Andrés Novo; David van Duin; Carolina Garcia-Vidal; Morgan Hakki; Isabel Ruiz-Camps; José Luis del Pozo; Chiara Oltolini; Catherine DeVoe; et al. (Microbiology Spectrum, 2022)
ABSTRACT We sought to assess the characteristics and outcomes of neutropenic hematologic patients with Pseudomonas aeruginosa (PA) bloodstream infection (BSI) treated with ceftolozane-tazobactam (C/T). We conducted a multicenter, international, matched-cohort study of PA BSI episodes in neutropenic hematologic patients who received C/T. Controls were patients with PA BSI treated with other antibiotics. Risk factors for overall 7-day and 30-day case fatality rates were analyzed. We compared 44 cases with 88 controls. Overall, 91% of episodes were caused by multidrug-resistant (MDR) strains. An endogenous source was the most frequent BSI origin (35.6%), followed by pneumonia (25.8%). There were no significant differences in patient characteristics between groups. C/T was given empirically in 11 patients and as definitive therapy in 41 patients. Treatment with C/T was associated with less need for mechanical ventilation (13.6% versus 33.3%; P = 0.021) and reduced 7-day (6.8% versus 34.1%; P = 0.001) and 30-day (22.7% versus 48.9%; P = 0.005) mortality. In the multivariate analysis, pneumonia, profound neutropenia, and persistent BSI were independent risk factors for 30-day mortality, whereas lower mortality was found among patients treated with C/T (adjusted OR [aOR] of 0.19; confidence interval [CI] 95% of 0.07 to 0.55; P = 0.002). Therapy with C/T was associated with less need for mechanical ventilation and reduced 7-day and 30-day case fatality rates compared to alternative agents in neutropenic hematologic patients with PA BSI. IMPORTANCE Ceftolozane-tazobactam (C/T) has been shown to be a safe and effective alternative for the treatment of difficult to treat infections due to Pseudomonas aeruginosa (PA) in the general nonimmunocompromised population. However, the experience of this agent in immunosuppressed neutropenic patients is very limited. Our study is unique because it is focused on extremely immunosuppressed hematological patients with neutropenia and bloodstream infection (BSI) due to PA (mainly multidrug resistant [MDR]), a scenario which is often associated with very high mortality rates. In our study, we found that the use of C/T for the treatment of MDR PA BSI in hematological neutropenic patients was significantly associated with improved outcomes, and, in addition, it was found to be an independent risk factor associated with increased survival. To date, this is the largest series involving neutropenic hematologic patients with PA BSI treated with C/T.